Insights into the value of seasonal climate forecasts to agriculture. (26th July 2020) - Darbyshire, Rebecca; Crean, Jason; Cashen, Michael; Anwar, Muhuddin Rajin; Broadfoot, Kim M; Simpson, Marja; Cobon, David H; Pudmenzky, Christa; Kouadio, Louis; Kodur, Shreevatsa
Abstract : Seasonal climate forecasts (forecasts) aim to reduce climate‐related productivity risk by helping farmers make decisions that minimise losses in poor years and maximise profits in good years. Most Australian forecast valuations have focused on fertiliser decisions to wheat operations, and few assessments have evaluated the benefit of incremental improvements of forecast skill. These gaps have limited our understanding of forecast value to the broader agriculture sector and the benefit of investments to improve forecast skill. To address these gaps, we consistently assessed forecast value for seven Australian case studies (southern grains, northern grains, southern beef, northern beef, lamb, cotton, and sugar). We implemented a three‐stage methodology which consisted of engagement with industry practitioners; modelling production under different climatic and environmental conditions; and economic modelling to evaluate forecast value for eleven levels of forecast skill. Our results show that forecast value was often low and highly variable. Value was found to vary based on forecast attributes (forecast skill, resolution and state), industry application and prevailing conditions (environmental and market). This is the first Australian valuation study where the same methodological approach was applied across multiple industries, incremental improvements in skill were valued, and prevailing conditions were explicitly evaluated for impact on value.